Postinfection Irritable Bowel Syndrome: The Links Between Gastroenteritis, Inflammation, the Microbiome, and Functional Disease. Issue 10 (November 2017) - Downs, Ian A.; Aroniadis, Olga C.; Kelly, Libusha; Brandt, Lawrence J.
Abstract : Postinfection irritable bowel syndrome (PI-IBS) is a diarrheal disease that develops after infectious gastroenteritis (IGE). Profound alterations in the microbiota accompany IGE yet only 10% of IGE patients progress to PI-IBS. This review explores research linking IGE severity, psychological comorbidity, PI-IBS, and the microbiome in various patient populations. Selective pressures caused by inflammation and increased gastrointestinal motility during gastroenteritis can alter intestinal bacterial phyla including Bacteroidetes, Firmicutes, and Proteobacteria. More specifically, classes such as Bacteroides and Clostridia are differentially abundant in many PI-IBS patients. Altered microbiota may perpetuate a cycle of enteric and systemic inflammation, potently activating neural afferent signaling in the enteric nervous system and causing pain and diarrhea in PI-IBS patients. Altered production of microbial metabolites, for example short chain fatty acids, may have enteric and systemic effects on the host. Longitudinal sampling to characterize changes in the microbiota's genetic, metabolic, and transcriptional activities over time from IGE to PI-IBS may enable improved diagnosis and classification of PI-IBS cases into subtypes, allowing for targeted antibiotic, probiotic, and prebiotic treatments. PI-IBS is a heterogenous and largely organic disease marked by specific alterations in functions of the microbiota and is an important model for studying microbial influences on intestinal, neurological, and psychological host functions.